295 CPR Performance with use of a CPR Feedback Device. (1st May 2022) - White, AE; Poh, JS; Lum, N; Jalil, A; Kua, PHJ; Ong, MEH
Abstract : Background: Quality cardiopulmonary resuscitation (CPR) correlates to out-of-hospital cardiac arrest (OHCA) survival. A real-time feedback device can guide rescuers towards delivering quality CPR. This study reports results of CPR quality during practice and during emergency use. Method: Rescuers in 17 OHCA cases used the CPRcard, a real-time feedback device, that they received/used during their CPR training. Corresponding weighted average of CPR quality measures (rate and depth) during training sessions were computed for comparison. Optimal CPR rate and depth in Singapore are 100–120cpm and 40–60mm, respectively. Paired t-tests were used for analysis. Results: There was no difference in average compression rate between practice (109.69) and emergency use (110.94; p=0.72). There was a significant difference in average compression depth (practice 48.20mm vs emergency 41.42mm; t(16)=2.24, p<0.05). During emergency use, the majority depth was in the <40mm range (practice 10.88% vs emergency 43.25%; t(15)=-3.47, p<0.01). Majority depth during practice was in the optimal range of 40–60mm (practice 83.69% vs emergency 49.13%; t(15)=4.21, p<0.01). Majority rate during practice was in the optimal range of 100–120 (practice 94.69% vs emergency 64.82%; t(16)=3.64, p<0.01). Majority rate during emergency use was above the optimal range (practice 4.0% vs emergency 23.76%; t(16)=-2.66, p<0.05). Conclusion: The CPRcard helped guide CPR performance considering that on average rate and depth were kept within standard. Nonetheless, CPR quality during emergencies slightly worsened vs. training. Fatigue induced leaning was possible as emergency CPR duration was longer (average time for practice 136.18 seconds vs emergency 351.06 seconds; t(16)=-3.07, p<0.01). Conflict of interest: None. Funding: Ministry of Health, Singapore.